A Decision Algorithm for Linear Isomorphism of Types with Complexity Cn(log2(n)) - Andreev, Alexander E.; Soloviev, Sergei (BRICS Report Series, 1996)
It is known that ordinary isomorphisms (associativity and commutativity of "times", isomorphisms for "times" unit and currying) provide a complete axiomatisation for linear isomorphism of types. One of the reasons to consider linear isomorphism of types instead of ordinary isomorphism was that better complexity could be expected. Meanwhile, no upper bounds reasonably close to linear were obtained. We describe an algorithm deciding if two types are linearly isomorphic with complexity Cn(log2(n)).